Identification Of Key Factors For Boosting To Increase Rice Production: Case Study In Merauke Regency, South Papua Province, Indonesia - Ineke Nursih Widyantari; Retnowati Wiranto; Gerzon J Maulany; Stanly HD Loppies (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Kurik District is one of the rice centers in Merauke Regency, South Papua Province. From 2019 to 2023, the . If allowed to continue, it will result in food shortages. Therefore, it is necessary to identify factors that can increase rice production. This study aims to determine the factors that affect rice production and to determine the factors that have a dominant influence on rice production.  This research was conducted in Kurik District, Merauke Regency, from June to August 2023. The types of data used are primary data and secondary data. Primary data was obtained from interviews, questionnaires, and observations. Secondary data is obtained from B.P.S. and other literature. The number of samples in this study was 473 rice farmers in Kurik District, Merauke Regency. Factors affecting rice production in Kurik District of Merauke Regency are land variables (0.312), seed variables (0.179), fertilizer variables (-0.143), and labor variables (0.290), while the dominant factor affecting rice production in Kurik District of Merauke Regency is the land variable (0.312). In this study, the factors that influence rice production have low values. Therefore, it is necessary to research to find other variables that significantly influence rice production in Kurik District, Merauke Regency.